The Benefits of Rumah Pintar Bangjo Central Java toward The Independence of Street Children in Pungkuran Village, Semarang - Iswara, Astuti Eka Stya; Arsal, Thriwaty; Pujiati, Amin (Universitas Negeri Semarang, 2020)
The purpose of this study is to assess the benefits of implantation on the independence of children assisted Smart House Bang Jo PKBI Central Java. This study used qualitative research methods. Research location in Kp. Pungkuran No. 403 Kauman, Semarang City. Data analysis techniques are carried out inductively, where the mindset is repeated based on observing specific problems and then drawing on general conclusions. The results of the study showed the planting of independence by the Smart House of Bang Jo PKBI Central Java through the activities of making headscarves (brooches), key chains, soccer, futsal, study groups, coloring, singing, reading and solving problems together.